Partition member and battery pack
A partition member combining powdered and fibrous inorganic substances with a specific density and structure maintains heat resistance and insulation under pressure, addressing the issue of heat transfer and safety in assembled batteries.
Patent Information
- Application Number
- JP2023093995
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-11-30
- Filing Date
- 2023-06-07
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2038-11-30
AI Technical Summary
Existing partition members in assembled batteries fail to maintain desired heat resistance and heat insulation properties under pressure, especially when secondary batteries expand due to charging/discharging or high temperatures, leading to potential chain reactions and damage.
A partition member composed of a combination of powdered inorganic substances and fibrous inorganic substances, with a density of 0.23 to 1.10 g/cm³, which includes a heat-insulating material that is porous and capable of retaining liquid, housed in an exterior body.
The partition member effectively maintains heat resistance and insulation properties even under pressure, preventing heat transfer and protecting adjacent cells from abnormal temperatures, thereby enhancing the safety of assembled batteries.
Smart Images

Figure 0007605249000003 
Figure 0007605249000004 
Figure 0007605249000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a partition member and a battery pack.
[0002] In recent years, secondary batteries have been rapidly used as power sources for vehicles and the like, and studies are being conducted to increase the energy density of secondary batteries in order to improve the degree of freedom when installing them in limited spaces such as vehicles and to extend the driving distance that can be traveled on a single charge. On the other hand, the safety of secondary batteries tends to be in conflict with their energy density, and the higher the energy density of the secondary battery, the lower the safety tends to be. For example, in the case of secondary batteries installed in electric vehicles with driving ranges of several hundred kilometers, if the secondary battery is damaged due to overcharging or an internal short circuit, the surface temperature of the battery may exceed several hundred degrees Celsius, and may even reach nearly 1000 degrees Celsius.
[0003] Since secondary batteries used as power sources for vehicles and the like are generally used as assembled batteries consisting of multiple cells, if one of the cells constituting the assembled battery is damaged and reaches the temperature range described above, the heat generated by the damaged cells may damage the adjacent cells, causing a chain reaction of damage to the entire assembled battery. In order to prevent such a chain reaction of damage between the cells, various techniques have been proposed, such as providing a partition member between the cells to cool the damaged cell, or providing a heat insulating material between the cells as a partition member.
[0004] For example, there is a battery with a cooler in which a secondary battery is placed in contact with a cooling container filled with a porous membrane and a cooling liquid in order to cool a battery that has abnormally generated heat (for example, Patent Document 1). There is also an energy storage element in which a partition member having a spacer made of a thermosetting resin and a base material made of a material that can melt in response to a temperature rise is placed between the energy storage elements (for example, Patent Document 2). On the other hand, there is also disclosed a partition member that uses an inorganic heat insulating material for separating the unit cells (for example, Patent Document 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-131428 A [Patent Document 2] JP 2010-97693 A [Patent Document 3] U.S. Patent No. 6,146,783 Summary of the Invention [Problem to be solved by the invention]
[0006] Regarding the above-mentioned conventional technology, the cooling container described in Patent Document 1 has a structure that opens when the secondary battery becomes abnormally hot and releases a cooling liquid to cool it. Also, the partition member described in Patent Document 2 has a structure that absorbs heat from the electricity storage element by the heat of melting of the meltable base material. However, when the cooling by the cooling liquid or the base material absorbing heat is insufficient, it is preferable that the membrane-shaped porous body or the thermosetting resin functions as a heat insulator and insulates against the heat from the abnormally hot secondary battery. However, in the conventional technology, the heat resistance and heat insulation of the membrane-shaped porous body or the thermosetting resin have not been sufficiently considered.
[0007] Patent Document 3 describes that the heat insulating property and flexibility are improved by using an inorganic material as a partition member. However, according to the study by the present inventors, it was found that, depending on the type of inorganic material, the moldability may be poor, the inorganic material may be easily deformed by compression, and the insulating property may be reduced at high temperatures even if the inorganic material has excellent insulating property at room temperature.
[0008] In particular, the following points are not taken into consideration in the prior art: For example, multiple secondary batteries may be arranged in the thickness direction and housed in a housing with pressure being applied in the thickness direction. In this case, pressure is also applied to partition members sandwiched between the secondary batteries and partition members arranged between the secondary batteries and members other than the secondary batteries. Secondary batteries are known to expand when charged and discharged or exposed to high temperatures, and pressure due to the expansion of the secondary batteries is also applied to the partition members. It is desirable for the partition members to maintain suitable heat resistance and heat insulation even in such an environment where the partition members are subjected to pressure.
[0009] An object of the present invention is to provide a partition member and a battery pack that are capable of maintaining desired heat resistance and thermal insulation even in a pressure environment. [Means for solving the problem]
[0010] [1] A partition member for separating a cell from another cell or between a cell and a member other than the cell, which contains a powdered inorganic material and a fibrous inorganic material and has a density of 0.23 to 1.10 g / cm 3 A partition member comprising an insulating material. [2] The partition member described in [1], wherein the insulating material is a porous material. [3] The partition member according to [1] or [2], wherein the powdered inorganic material is at least one selected from silica particles, alumina particles, calcium silicate, and vermiculite. [4] A partition member according to any one of [1] to [3], wherein the fibrous inorganic material is at least one selected from glass fiber, rock wool, ceramic fiber and biosoluble inorganic fiber.
[0011] [5] A battery pack including a plurality of unit cells and the partition member according to any one of [1] to [4]. Effect of the Invention
[0012] According to the present invention, there are provided a partition member capable of maintaining desired heat resistance and thermal insulation even in a pressure environment, and a battery pack using the same. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 shows an example of the configuration of a partition member of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of the partition member shown in FIG. 1 taken along line AA. [Diagram 3] FIG. 3 shows an example of a single cell. [Figure 4] FIG. 4 is a front view of the unit cell shown in FIG. [Diagram 5] FIG. 5 is a side view of the unit cell shown in FIG. [Figure 6] FIG. 6 is a top view showing an example of a battery pack. [Figure 7] FIG. 7 is a side view showing a schematic side view of the battery pack shown in FIG. 6 with the front side plate removed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described below. The following description of the embodiments shown in the drawings is merely an example, and the present invention is not limited to the configurations shown in the drawings.
[0015] <Partition material> The partition member of the present invention is a partition member that separates unit cells or separates unit cells from components other than unit cells, and contains a powdered inorganic material and a fibrous inorganic material and has a density of 0.23 to 1.10 g / cm. 3 The partition member is characterized in that it contains a heat insulating material having the above-mentioned characteristic. In addition, it is preferable that the heat insulating material is a porous body and capable of retaining liquid. Furthermore, the partition member may be made of only a heat insulating material as long as it contains a heat insulating material having the above-mentioned characteristic, but a preferred embodiment is one in which the heat insulating material is contained in an exterior body.
[0016] By including the insulating material in the partition member, it is possible to prevent the heat resistance and heat insulation of the insulating material from being significantly reduced or lost due to pressure applied to the partition member. In other words, the insulating material of the partition member that receives heat from the secondary battery maintains the desired heat resistance and heat insulation, making it possible to block heat transfer to other secondary batteries, etc.
[0017] Fig. 1 shows an example of the configuration of a partition member of the present invention. Fig. 1 shows a front view of a partition member 1. Fig. 2 shows a cross section of the right side of the partition member shown in Fig. 1 taken along line AA.
[0018] 1 and 2, the partition member 1 has a flat or sheet-like overall shape having a height direction (H), a width direction (W), and a thickness direction (D). The partition member 1 has a thickness direction (D) and a plane direction (P) perpendicular to the thickness direction (D). The plane direction (P) includes the height direction (H) and width direction (D) described above, as well as a plurality of oblique directions between the height direction (H) and the width direction (D).
[0019] The partition member 1 is used to separate the cells constituting the battery pack, or between the cells and members other than the cells, in its thickness direction (D). The partition member 1 includes a heat insulating material 110, and preferably includes an exterior body 120 that houses the heat insulating material 110 capable of retaining liquid.
[0020] [Thermal insulation] The heat insulating material 110 includes powdered inorganic materials and fibrous inorganic materials. In the present invention, "fibrous inorganic materials" refers to inorganic materials having a shape in which the major axis is 100 times or more larger than the minor axis, and "powdered inorganic materials" refers to inorganic materials having a shape in which the major axis is less than 100 times larger than the minor axis. In particular, in the case of fibrous materials, the "major axis" refers to the fiber length, and the "minor axis" refers to the diameter of a cross section perpendicular to the major axis direction.
[0021] If the insulating material used in the partition member is composed only of powdered inorganic matter, the insulating material has poor moldability and is difficult to maintain its shape, so it is necessary to solidify it using a binder, etc. If such a partition member is placed in an environment where it is subjected to pressure and compressed, it becomes difficult to maintain its shape, which in turn deteriorates its heat resistance.
[0022] On the other hand, if the insulating material used for the partition member is composed only of fibrous inorganic matter, the insulating properties tend to be high due to the air spaces between the fibers that make up the insulating material, but the insulating properties decrease due to the influence of thermal radiation at high temperatures. Also, when the partition member is placed in an environment where it is subjected to pressure and compressed, there is a problem that it is easily deformed by compression.
[0023] The heat insulating material used in the partition member of the present invention overcomes the above problems by using a combination of a powdered inorganic material and a fibrous inorganic material.
[0024] The fibrous inorganic material is preferably at least one selected from the group consisting of paper, cotton sheet, polyimide fiber, aramid fiber, polytetrafluoroethylene (PTFE) fiber, glass fiber, rock wool, ceramic fiber, and biosoluble inorganic fiber, and among these, at least one selected from glass fiber, rock wool, ceramic fiber, and biosoluble inorganic fiber is particularly preferable. The ceramic fiber is a fiber mainly composed of silica and alumina (silica:alumina=40:60 to 0:100), and specifically, silica-alumina fiber, mullite fiber, and alumina fiber can be used.
[0025] Examples of powdered inorganic substances include silica particles, alumina particles, calcium silicate, clay minerals, vermiculite, mica, cement, perlite, fumed silica, and aerosols. It is preferable that the clay mineral is at least one selected from the group consisting of gels, and among these, it is particularly preferable that the clay mineral is at least one selected from silica particles, alumina particles, calcium silicate, and vermiculite. Among the types of calcium silicate, xonotlite, tobermorite, wollastonite, and gyrolite are preferable, and gyrolite is particularly preferable. Gyrolite, which has a petal-like structure, maintains its porous structure even when compressed and deformed, and therefore has excellent liquid retention properties. Clay minerals are mainly magnesium silicate (including talc and sepiolite), montmorillonite, and kaolinite.
[0026] The insulating material containing fibrous inorganic matter and powdery inorganic matter can be selected from known materials that satisfy a predetermined density and used. For example, it can be selected from those described in JP-A-2003-202099.
[0027] The density of the insulation material is 0.23 to 1.10 g / cm3 in order to be lightweight and maintain its insulation properties even at high temperatures. 3 When the density of the heat insulating material is equal to or higher than the lower limit, the internal voids have many air layers, which is preferable from the viewpoint of heat insulating property and liquid retention, whereas when the density is equal to or lower than the upper limit, the amount of deformation during compression is small, which is preferable. From these viewpoints, the density of the heat insulating material is preferably 0.35 g / cm 3 More preferably, it is 0.55 g / cm 3 or more, while preferably 1.05 g / cm 3 More preferably, it is 1.00 g / cm 3 The following is the result.
[0028] It is preferable that the entire heat insulating material 110 is formed of a porous body. In the following description, the entire heat insulating material 110 is formed of a porous body, and the liquid is held in the cavities of the porous body. It is preferable that the heat insulating material 110 has elasticity so that it can respond to pressure. However, there are cases where the heat insulating material does not have elasticity.
[0029] 〔liquid〕 When the porous body is made to retain a liquid, the liquid to be used is preferably a liquid having a boiling point at normal pressure of 80°C or more and 250°C or less, more preferably a liquid having a boiling point at normal pressure of 100°C or more and 150°C or less. Specific examples of the liquid to be used include, in addition to water, at least one selected from the group consisting of alcohols, esters, ethers, ketones, hydrocarbons, fluorine-based compounds, and silicone-based oils. These may be used alone or as a mixture of two or more. The liquid may contain additives such as a substance that imparts antifreeze (antifreeze agent), a preservative, and a pH adjuster. By imparting antifreeze, it is possible to prevent the exterior body from being damaged by expansion caused by freezing. In addition, by adding a pH adjuster, the pH of the liquid changes due to components eluted from the powdered inorganic material, and the like, and the possibility of the powdered inorganic material, the exterior body, and the liquid (water) itself being altered can be reduced. The substances contained in the water are not limited to these, and can be added as necessary.
[0030] [Exterior body] The exterior body 120 contains the liquid and the heat insulating material 110 in a sealed state. For example, a film or sheet made of resin or metal can be applied as the exterior body 120. For example, it is preferable to laminate the heat insulating material holding the liquid using a film or sheet made of a metal and a resin in order to obtain high heat resistance and strength. As a laminate having a laminated structure of metal and resin used in the above lamination, it is preferable to apply a laminate having three or more layers including a resin layer, a metal layer, and a resin sealant layer. Examples of metals include aluminum foil, copper foil, tin foil, nickel foil, stainless steel foil, lead foil, tin-lead alloy foil, bronze foil, silver foil, iridium foil, and phosphorus bronze foil. In particular, aluminum foil, copper foil, and nickel foil are preferable, and aluminum foil is more preferable. It is preferable that the metal is at least one selected from the examples listed above.
[0031] As the resin, at least one of a thermosetting resin and a thermoplastic resin can be used. However, it is preferable to use a thermoplastic resin. Examples of the resin include polyethylene, polypropylene, polystyrene, nylon, acrylic, epoxy resin, polyurethane, polyether ether ketone, polyethylene terephthalate, polyphenylene sulfide, polycarbonate, and aramid. In particular, at least one selected from polypropylene, nylon, and polyethylene terephthalate is preferable.
[0032] The thickness of the exterior body 120 is not particularly limited, but is, for example, 5 μm to 200 μm. In the case of the above laminate, the metal foil can be 3 μm to 50 μm thick, and the resin layer can be 2 μm to 150 μm thick. This allows the heat resistance and low water vapor permeability of the metal foil to be exhibited, while the resin can improve the sealing performance.
[0033] Furthermore, the outer casing 120 is formed by joining the peripheral portions of two outer casings into a ring shape by heat fusion, adhesion, or the like, so that the heat insulating material 110 is hermetically sealed within the outer casing 120. Alternatively, one outer casing may be folded and the peripheral portions joined by heat fusion, adhesion, or the like, to hermetically seal the liquid and the heat insulating material 110. The outer casing 120 is preferably flexible (elastic), but may not be flexible in some cases.
[0034] In the example shown in FIG. 1, the exterior body 120 is provided with a sealing portion 120a that seals the periphery thereof, and the heat insulating material 110 is housed in an internal space 111 formed in the exterior body 120 by sealing with the sealing portion 120a. In the example shown in FIG. 1, a gap 120b is provided between the sealing portion 120a and the heat insulating material 110 in the internal space 111. In other words, the internal space 111 includes a first region S1 where the exterior body 120 and the heat insulating material 110 overlap, and a second region S2 where the exterior body 120 and the heat insulating material 110 do not overlap, in a plan view of the front of the partition member 1. However, the gap 120b is not necessarily required. The gap 120b may be in a state where the inner surfaces of the exterior body 120 are in contact with each other when no fluid (gas or liquid) is present therein. In the present invention, the volume of the internal space 111 is defined as the product of the area of the internal space 111 and the thickness of the heat insulating material 110. Furthermore, the heat insulating material does not necessarily have to be disposed in the center of the interior space, and it does not necessarily have to be parallel to the exterior body.
[0035] <Battery pack> Next, a battery pack to which the partition member 1 is applied will be described. The battery pack is applied to, for example, battery packs mounted on electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), heavy electric machinery, electric motorcycles, power-assisted bicycles, ships, aircraft, trains, uninterruptible power supplies (UPSs), home power storage systems, power system stabilization battery systems that utilize renewable energy such as wind, solar, tidal, and geothermal energy, and the like. However, the battery pack can also be used as a power source that supplies power to devices other than the above-mentioned EVs.
[0036] [Battery] Fig. 3 is a plan view showing an example of a unit cell constituting a battery pack, Fig. 4 is a front view of the unit cell shown in Fig. 3, and Fig. 5 is a right side view of the unit cell. The unit cell 200 is formed in a rectangular parallelepiped shape having a height direction (H), a width direction (W), and a thickness direction (D), and terminals 210 and 220 are provided on the upper surface. The unit cell 200 is, for example, a lithium ion secondary battery including a positive electrode and a negative electrode capable of absorbing and releasing lithium ions, and an electrolyte. Other than the lithium ion secondary battery, secondary batteries such as a lithium ion solid-state battery, a nickel hydrogen battery, a nickel cadmium battery, and a lead storage battery can be used.
[0037] [Battery pack] Fig. 6 shows a top view of a battery pack 100 formed using a plurality of unit cells 200, and Fig. 7 is a side view showing a state in which a side plate 300d is removed from the battery pack 100 shown in Fig. 6. In Figs. 6 and 7, the battery pack 100 includes a housing 300 and a plurality of unit cells 200 housed in the housing 300. The housing 300 has a bottom plate 300e and side plates 300a, 300b, 300c, and 300d erected along the outer periphery of the bottom plate 300e. In Figs. 6 and 7, five unit cells 200 are shown as an example, but the number of unit cells can be selected as appropriate.
[0038] In the casing 300, the plurality of single cells 200 are arranged in the thickness direction, and the above-mentioned partition member 1 is disposed between the single cells 200. The positive terminal (e.g., terminal 210) and the negative terminal (e.g., terminal 220) of adjacent (facing) single cells 200 via the partition member 1 are electrically connected in series by the bus bar 301, and the battery pack 100 outputs a predetermined power. As shown in FIG. 7, in the battery pack 100, a partition member 1A is disposed between the upper surface of the bottom plate 300e of the casing 300 and each of the single cells 200. The partition member 1A has a similar configuration to the partition member 1.
[0039] <Heat generation and heat transfer in battery packs> Some or all of the chemical substances constituting the electrodes, electrolyte, etc., constituting the cell 200 may undergo a decomposition reaction accompanied by heat generation inside the cell 200, causing the temperature of the cell 200 to rise, and some or all of the regions of the cell 200 may reach 200° C. or higher. In the present invention, this state is referred to as an "abnormal heat generation state."
[0040] It is generally known that the safety of the positive electrode material among the materials constituting the single cell 200 is greatly affected by the stability of the crystal structure after lithium removal by charging. 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.8 Co 0.15 Al 0.05 Materials such as 02 and 03 undergo crystal collapse accompanied by oxygen release at high temperatures in a charged state. The oxygen released from the positive electrode causes oxidation of the electrolyte, etc., which is accompanied by a rapid exothermic reaction. It has been reported that the above positive electrode materials undergo a crystal phase transition at around 200°C through structural analysis using synchrotron radiation. Therefore, when a part or the entire region of the single cell 200 reaches 200°C or higher, it means that the crystal collapse of the positive electrode is progressing, that is, the single cell 200 is in a thermal runaway state (Reference 1: High Safety Technology and Materials for Lithium-Ion Batteries, CMC Publishing, p. 44 / Reference 2: J. Dahn et al., Electrochemistry Communication, 9, 2534-2540 (2007) / Reference 3: Hironori Kobayashi, "Evaluation and Analysis Technology for Lithium-Ion Secondary Battery Positive Electrode Materials Using Synchrotron Radiation," Spring-8 Promotion Council Glass and Ceramics Study Group (2nd) (2011)).
[0041] In addition, regarding the safety of the negative electrode material among the materials constituting the single cell 200, it is known that the charging negative electrode (lithium-intercalated carbon negative electrode) basically exhibits strong reducing properties similar to those of lithium metal, and a coating is formed on the surface of the negative electrode by reaction with the electrolyte, thereby suppressing further reactions. Therefore, the chemical composition, structure, and thermal stability of the protective coating have a significant effect on the thermal stability of the charging negative electrode when the temperature rises. Usually, the reaction between the charging negative electrode and the electrolyte is explained by the formation of a protective coating, followed by an explosive reduction decomposition reaction due to the destruction of the coating. It has been reported that, in general, the protective coating formation reaction on the negative electrode begins at around 130°C, followed by a coating decomposition reaction at around 200°C, ultimately leading to an explosive reduction decomposition reaction. For this reason, when a part or the entire area of the single battery 200 reaches 200°C or higher, it means that destruction of the coating on the surface of the negative electrode is progressing, that is, the single battery 200 is in a state of thermal runaway (Reference 4: Battery Handbook, 1st Edition, Ohmsha, p. 591 / Reference 5: The Cutting Edge of High Safety Technology and Evaluation Technology for Lithium-Ion Batteries, CMC Publishing, p. 90).
[0042] In the present invention, a state in which chemical substances constituting the electrodes, electrolyte, etc. constituting the single cell 200 are not undergoing a decomposition reaction accompanied by a certain heat generation rate or higher inside the single cell 200 is referred to as a "normal state". Here, the heat generation state of the single cell 200 can be evaluated using ARC (Accelerating Rate Calorimetry), which is a means for quantitatively measuring the thermal behavior when a reactive chemical substance self-heatingly decomposes under adiabatic conditions. For example, Dahn et al. define that a self-heating reaction is proceeding inside the cell when the heat generation rate observed in ARC exceeds 0.04°C / min, and this can be followed (Reference 6: J. Dahn et al., Electrochimica Acta, 49, 4599-4604 (2004)). In the present invention, a single cell 200 in a normal state is referred to as a "single cell that maintains a normal state", and a single cell 200 that has deviated from the normal state and has not reached an abnormal heat generation state is referred to as a "single cell that deviates from the normal state". Heat generated inside the unit cells 200 is transmitted through various transmission paths to other unit cells 200. For example, heat generated inside the unit cells 200 can be transmitted to other unit cells 200 through the partition member 1.
[0043] For example, the upper limit of the average surface temperature that is expected when the cell 200 in contact with or close to the partition member 1 deviates from the normal state and does not reach an abnormal heat generation state is set to 180° C. Here, when the general-purpose separator material is made of polyethylene or polypropylene, it is known that the meltdown temperature is 160 to 200° C. Therefore, when the average surface temperature of the cell 200 exceeds 180° C., there is a risk that a part of the general-purpose separator material constituting the cell 200 will melt down, leading to an abnormal heat generation state.
[0044] In a range where the average temperature of one of the two thickness-wise faces of the partition member 1 separating the cells 200 constituting the battery pack 100 does not exceed 100°C, the partition member 1 can transmit heat from the cells 200 (e.g., the cell 200a) in the battery pack 100 in its thickness direction, and transmit it to other cells 200 (cell 200b) facing the cell 200a via the partition member 1, or to members other than the cells 200 (e.g., the bottom plate 300e). In contrast, when the average temperature exceeds 100°C, the partition member 1 opens due to heat, and the contained liquid flows out to the outside in a gaseous or liquid phase state. This flow causes air (which has a thermal insulating effect) to enter the insulating material 110 in the partition member 1, increasing the insulating property (thermal resistance) in the thickness direction. This makes it possible to prevent other cells 200 from becoming out of their normal state due to a certain cell 200 becoming out of their normal state.
[0045] The upper limit of the average surface temperature of the cells 200 in contact with or close to the partition member 1 is usually 80° C. when the cells 200 are not out of the normal state. The boiling points of the general-purpose electrolyte components are 90° C. or higher, as shown in Table 1 below. Examples of the general-purpose electrolyte components are ethylene carbonate (EC), diethyl carbonate, dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC). When the average surface temperature of the cells 200 is lower than 80° C., the general-purpose electrolyte constituting the cells 200 does not boil. When the average temperatures of both of the two thickness-wise surfaces of the partition member 1 separating the cells constituting the battery pack are lower than 80° C., the contained liquid promotes heat transfer in the thickness direction. When all of the cells 200 constituting the battery pack 100 are in a normal state, the heat transfer resistance of the partition member 1 is lower than that of conventional products, which is effective in equalizing the temperature between the cells 200 in the battery pack 100 and is expected to reduce deterioration of the cells 200 due to temperature unevenness.
[0046] [Table 1] EXAMPLES
[0047] Next, an embodiment of the present invention will be described. Example 1 As the heat insulating material 110, vermiculite paper (height 50 mm, width 50 mm, thickness 2 mm, density 0.85 g / cm 3 A porous body containing vermiculite (powdered inorganic material) and glass fiber (fibrous inorganic material) was prepared.
[0048] (1) Room temperature thermal conductivity measurement Using the above-mentioned heat insulating material, the heater, brass plate, heat insulating plate A (Misumi Corporation, model: HIPHA, thickness 10 mm), brass plate, porous body, brass plate, heat insulating plate A, brass plate, heat insulating plate B (Misumi Corporation, model: HIPHA, thickness 40 mm) were sandwiched in this order to adhere each component, and the above-mentioned heat insulating material was used as a partition member. The load was adjusted to 375 kg (15 kgf / cm) from above the heat insulating plate B using a hydraulic press machine HYP505H (manufactured by Japan Automatic Machine Co., Ltd.). 2 (equivalent to).
[0049] With the above load applied, the heater temperature was raised to 80°C, and after the heater temperature reached 80°C, heating was continued at that temperature for 30 minutes. After heating was completed, the thickness (referred to as "film thickness") of the insulating material (partition member) was measured, and the film thickness when compressed was determined to be 1.8 mm. From the temperatures at each position at the end of heating, the thermal conduction resistance from the heater to the insulating material, and the film thickness of the insulating material when compressed, the room temperature thermal conductivity k L was calculated according to the following formula: k L = (ΔT1×L) / (ΔT2×R) k L : Thermal conductivity of insulation material [W / (m K)] ΔT1: Temperature difference between the hot and cold sides of insulation plate A [K] ΔT2: Temperature difference between the hot and cold sides of the insulation [K] L: thickness of insulation material when compressed [m] R: Thermal resistance from heater to insulation 6.8×10 -3 [m 2 K / W
[0050] Thermal conductivity k 30 minutes after the heater reaches 80°C L was 0.08 W / (m K).
[0051] (2) High-temperature thermal conductivity measurement Using the same insulating material as that used in the room temperature thermal conductivity measurement described above, the heater, brass plate (two of the same material were used in layers), insulating material, brass plate, insulating plate A, brass plate, and insulating plate B were stacked from the bottom in this order to bring each part into close contact, and the insulating material described above was used as a partition member. A hydraulic press was used to adjust the load from above insulating plate B to 375 kg (15 kgf / cm 2 (equivalent to).
[0052] With the load applied, the heater temperature was raised to 600°C, and after the heater temperature reached 600°C, heating at that temperature was continued for 1 hour. After heating was completed, the thickness of the heat insulating material (partition member) was measured, and the thickness at the time of compression was found to be 1.9 mm. The thermal conductivity of the insulation material, k, is calculated from the temperature, the thermal resistance from the heater to the insulation material, and the thickness of the insulation material when compressed. H was calculated according to the following formula: k H =(ΔT3 / Rq) × L / ΔT4 (formula) k H : Thermal conductivity of insulation material [W / (m K)] ΔT3: Temperature difference between the hot and cold sides of insulation plate A [K] ΔT4: Temperature difference between the hot and cold sides of the insulation [K] L: Compressed thickness of insulation (film thickness) [m] R: Thermal resistance from heater to insulation 1.65×10 -4 [m 2 K / W q: Heat loss due to convection and radiation from each brass plate and insulation material 1.35×10 4 [W / m 2 ]
[0053] In the above formula, the high temperature side and the low temperature side refer to the side closer to the heater and the opposite side, respectively. Thermal conductivity k after 1 hour has elapsed since the heater reached 600°C H was 0.08 W / (m K).
[0054] Example 2 Instead of the vermiculite paper in Example 1, a heat insulating sheet having a thickness of 2 mm (density 0.95 g / cm 3 The same experiment as in Example 1 was carried out using a porous material containing wollastonite (powdered inorganic material) and rock wool (fibrous inorganic material). In Example 2, the film thickness when compressed was 1.8 mm in the room temperature thermal conductivity measurement, and the film thickness when compressed was 1.9 mm in the high temperature thermal conductivity measurement.
[0055] Example 3 Instead of the vermiculite paper in Example 1, calcium silicate paper with a thickness of 1 mm (density 0.38 g / cm 3 The same experiment as in Example 1 was carried out using two layers of a porous material containing calcium silicate (powdered inorganic material) and rock wool (fibrous inorganic material). In Example 3, the thickness of the film when compressed was 1.9 mm in the room temperature thermal conductivity measurement, and the thickness of the film when compressed was 1.7 mm in the high temperature thermal conductivity measurement.
[0056] Example 4 Instead of the vermiculite paper in Example 1, calcium silicate paper with a thickness of 1 mm (density 0.25 g / cm 3 The same experiment as in Example 1 was carried out using two layers of a porous material containing calcium silicate and rock wool (a porous material containing calcium silicate and rock wool). In Example 4, the thickness of the compressed film in the room temperature thermal conductivity measurement was 1.7 mm, and the thickness of the compressed film in the high temperature thermal conductivity measurement was 1.6 mm.
[0057] Comparative Example 1 Instead of the vermiculite paper in Example 1, a glass fiber paper containing vermiculite with a thickness of 0.6 mm (density 0.22 g / cm 3The same experiment as in Example 1 was carried out using four laminated sheets of the porous body (compressed porous body). In Comparative Example 1, the film thickness when compressed was 1.4 mm in the room temperature thermal conductivity measurement, and the film thickness when compressed was 1.6 mm in the high temperature thermal conductivity measurement.
[0058] Comparative Example 2 Instead of the vermiculite paper in Example 1, a vermiculite-containing rock wool paper (density 1.16 g / cm) with a thickness of 0.9 mm was used. 3 The same experiment as in Example 1 was carried out using three laminated sheets of the porous body (compressed porous body). In Comparative Example 2, the film thickness when compressed was 2.0 mm in the room temperature thermal conductivity measurement, and the film thickness when compressed was 2.0 mm in the high temperature thermal conductivity measurement.
[0059] Comparative Example 3 Instead of the vermiculite paper in Example 1, a glass fiber paper with a thickness of 0.6 mm (density 0.125 g / cm 3 The same experiment as in Example 1 was carried out using four layers of the porous body. In Comparative Example 3, the film thickness when compressed in the room temperature thermal conductivity measurement was 1.4 mm, and the film thickness when compressed in the high temperature thermal conductivity measurement was 1.4 mm.
[0060] Comparative Example 4 Vermiculite powder (containing no fibrous inorganic matter) was used instead of the vermiculite paper used in Example 1. Vermiculite powder alone is poorly moldable and prone to deformation, so vermiculite powder was enclosed in an aluminum laminate film (containing polyethylene (inside), aluminum, and polyethylene terephthalate (outside), thickness 0.15 mm) (thickness 2 mm, density 0.6 g / cm3). 3 ) was used to carry out the same experiment as in Example 1. In Comparative Example 4, the film thickness when compressed in the room temperature thermal conductivity measurement was 1.7 mm, and the film thickness when compressed in the high temperature thermal conductivity measurement was 1.8 mm.
[0061] Comparative Example 5 Instead of the vermiculite paper in Example 1, a vermiculite paper with a thickness of 1.8 mm (density 1.56 g / cm3 The same experiment as in Example 1 was carried out using a porous material containing vermiculite and glass fiber (a porous material containing vermiculite and glass fiber). In Comparative Example 5, the film thickness when compressed was 1.8 mm in the room temperature thermal conductivity measurement, and the film thickness when compressed was 1.8 mm in the high temperature thermal conductivity measurement.
[0062] The densities and thermal conductivities of Examples 1 to 4 and Comparative Examples 1 to 5 are shown in Table 2 below. [Table 2]
[0063] Table 2 shows the relationship between the density and thermal conductivity of the insulating material used in each of the partition members obtained by the experiments according to the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 5. The experimental results show that the partition members of the present invention using a combination of powdered inorganic material and fibrous inorganic material have a lower high-temperature thermal conductivity value than Comparative Examples 3 and 4, and have better thermal insulation properties at high temperatures. The experimental results also show that the partition members of the present invention have a density of 0.22 g / cm 3 Comparative Example 1, in which the heat insulating material of 3 Comparative Example 2, in which the heat insulating material of 1.56 cm3 was used as the partition material, 3 It can be seen that the heat insulating material of the present invention, which contains a powdered inorganic substance and a fibrous inorganic substance and has a thermal conductivity of 0.23 g / cm3, is lower at high temperatures than that of the heat insulating material of the present invention, which contains a powdered inorganic substance and a fibrous inorganic substance and has a thermal conductivity of 0.23 g / cm3. 3 or more and 1.10g / cm 3 By applying a porous material having the density described below to the insulating material 110, it is possible to obtain an insulating material 110 that exhibits suitable heat resistance and insulating properties against temperatures that deviate from the normal state of a secondary battery, even when placed in an environment subjected to pressure.
[0064] The above-mentioned configurations can be combined as appropriate without departing from the scope of the invention. [Explanation of symbols]
[0065] 1 Partition material 100 battery packs 110 Insulation 120 Exterior body 200 Cells 300 Case
Claims
1. A partition member that separates the cells or separates the cells from components other than the cells, A thickness direction and a surface direction perpendicular to the thickness direction, An exterior body that contains a heat insulating material in a sealed state therein, When the sealed state is released by opening the exterior body, the thermal resistance in the thickness direction increases. Partition material.
2. The heat insulating material includes a powdered inorganic material and a fibrous inorganic material. The partition member according to claim 1 .
3. The density of the heat insulating material is 0.23 to 1.10 g / cm 3 That is, The partition member according to claim 1 .
4. The heat insulating material includes a powdered inorganic material and a fibrous inorganic material, The density of the heat insulating material is 0.23 to 1.10 g / cm 3 is The partition member according to claim 1 .
5. The partition member according to claim 1 , wherein the heat insulating material is a porous material.
6. 5. The partition member according to claim 2 or 4, wherein the powdered inorganic material is at least one selected from the group consisting of silica particles, alumina particles, calcium silicate, and vermiculite.
7. 5. The partition member according to claim 2 or 4, wherein the fibrous inorganic material is at least one selected from the group consisting of glass fiber, rock wool, ceramic fiber and biosoluble inorganic fiber.
8. A battery pack comprising a plurality of unit cells and the partition member according to claim 1 .
9. A method for manufacturing a battery pack including a plurality of single cells and a partition member, comprising: A method for manufacturing a battery pack, comprising disposing the partition member according to claim 1 between unit cells or between a unit cell and a member other than the unit cells.
10. A method for a partition member including an exterior body having a thickness direction and a surface direction perpendicular to the thickness direction and containing a heat insulating material in a sealed state therein, the method comprising: increasing the thermal resistance of the partition member in the thickness direction by releasing the sealed state by opening the exterior body.
Citation Information
Patent Citations
Safe battery pack
CN106784518A
Battery pack
JP2007134138A
Power storage device
JP2010097693A
Battery with cooling part
JP2013131428A
A method for thermally isolating battery cells in the event of a failure.
JP2013536542A
